Asymmetric Total Synthesis of (+)‐Ryanodol and (+)‐Ryanodine. Issue 1 (30th November 2015) - Masuda, Kengo; Koshimizu, Masaki; Nagatomo, Masanori; Inoue, Masayuki
Abstract: (+)‐Ryanodine (1 ) is the ester derivative of 1 H ‐pyrrole‐2‐carboxylic acid and the complex terpenoid (+)‐ryanodol (2 ), which possesses eleven contiguous stereogenic centers on the ABCDE‐ring system. Compound1 is known to be a potent modulator of intracellular calcium release channels, whereas the activity of2 is significantly weaker. To chemically construct1, the multiple oxygen functional groups must be installed on the fused pentacycle in stereoselective fashions and the extremely hindered C3‐hydroxy group must be acylated in a site‐selective manner. First, the total synthesis of2 was accomplished by introducing the five stereocenters from the previously prepared enantiopure ABDE‐ring7 . Stereoselective construction of the C3‐secondary, C2‐ and C6‐tertiary alcohols was achieved by three nucleophilic reactions. The C9‐ and C10‐trisubstituted carbon centers were regio‐ and stereoselectively introduced by hydroboration/oxidation of the six‐membered C‐ring, which was formed by the ring‐closing metathesis reaction. Direct esterification of the C3‐alcohol with pyrrole‐2‐carboxylic acid proved unsuccessful; therefore, we developed a new, two‐step protocol for attachment of the pyrrole moiety. The C3‐hydroxy group was first converted into the less sterically cumbersome glycine ester, which was then transformed into the pyrrole ring through condensation with 1, 3‐bis(dimethylamino)allylium tetrafluoroborate. This procedure resulted in the first total synthesis of1 . Abstract : Total synthesis of ryanodine, part 2 : (+)‐Ryanodine (1 ) is the ester derivative of 1 H ‐pyrrole‐2‐carboxylic acid and the complex terpenoid (+)‐ryanodol (2 ), which possesses eleven contiguous stereogenic centers on the pentacyclic ring system. The total synthesis of both2 and1 was realized from the enantiopure tetracycle. The new, two‐step protocol was developed to attach the pyrrole moiety onto the hindered alcohol, enabling the completion of the first chemical construction of1 (see scheme).